Novel fluorescence probe for estimation of cysteine/histidine in human blood plasma and recognition of endogenous cysteine in live Hct116 cells - Reddy, Upendar G.; Agarwalla, Hridesh; Taye, Nandaraj; Ghorai, Suvankar; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new Cu(II)-complex is used as a ``Turn-On'' luminescence probe for specific detection of endogenous Cys in live Hct116 cells and Cys present in human blood plasma without any interference from other amino acids, especially GSH and Hcy. Difference in the mechanistic pathway for Cys and His recognition is discussed.

Doxorubicin-conjugated beta-NaYF4:Gd3+/Tb3+ multifunctional, phosphor nanorods: a multimodal, luminescent, magnetic probe for simultaneous optical and magnetic resonance imaging and an excellent pH-triggered anti-cancer drug delivery nanovehicle - Padhye, Preeti; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Sarnit; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report the fabrication of a multifunctional nanoprobe based on highly monodispersed, optically and magnetically active, biocompatible, PEI-functionalized, highly crystalline beta-NaYF4:Gd3+/Tb3+ nanorods as an excellent multi-modal optical/magnetic imaging tool and a pH-triggered intracellular drug delivery nanovehicle. The static and dynamic photoluminescence spectroscopy showed the presence of sharp emission peaks, with long lifetimes (similar to 3.5 milliseconds), suitable for optical imaging. The static magnetic susceptibility measurements at room temperature showed a strong paramagnetic signal (chi similar to 3.8 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed fair T-1 relaxivity (r(1) = 1.14 s(-1) mM(-1)) and magnetic resonance imaging gave enhanced T-1-weighted MRI images with increased concentrations of beta-NaYF4:Gd3+/Tb3+ making them suitable for simultaneous magnetic resonance imaging. In addition, an anticancer drug, doxorubicin (DOX) was conjugated to the amine-functionalized beta-NaYF4:Gd3+/Tb3+ nanorods via pH-sensitive hydrazone bond linkages enabling them as a pH-triggered, site-specific drug delivery nanovehicle for DOX release inside tumor cells. A comparison between in vitro DOX release studies undertaken in normal physiological (pH 7.4) and acidic (pH 5.0) environments showed an enhanced DOX dissociation (similar to 80%) at pH 5.0. The multifunctional material was also applied as an optical probe to confirm the conjugation of DOX and to monitor DOX release via a fluorescence resonance energy transfer (FRET) mechanism. The DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods exhibited a cytotoxic effect on MCF-7 breast cancer cells and their uptake by MCF-7 cells was demonstrated using confocal laser scanning microscopy and flow cytometry. The comparative cellular uptakes of free DOX and DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods were studied in tumor microenvironment conditions (pH 6.5) using confocal imaging, which showed an increased uptake of DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods. Thus, DOX-conjugated beta-NaYF4:Get(3+)/Tb3+ nanorods combining pH-triggered drug delivery, efficient luminescence and paramagnetic properties are promising for a potential multifunctional platform for cancer therapy, biodetection, and optical and magnetic resonance imaging.

Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.